Mankind and energy : needs, resources, hopes : proceedings of a Study Week at the Pontifical Academy of Sciences, November 10-15, 1980 - Blanc-Lapierre, A. (Andre), 1915-2001 (Studies in environmental science, 1982)
Mankind and energy : needs, resources, hopes.